CUT PICK CUT LINE DISTRIBUTION AND THE FINDINGS OF A STUDY OF LOAD SPECTRUM - HAO ZhiYong; ZHANG Pei; SONG ZhenDuo (Jixie qiangdu)
According to studying Angle cutting conditions of shearer drum cutting teeth distribution on the influence law of load spectrum,which provides reference for the design of the cutter tooth,in which equivalent test tooth holder to roll the same spiral blades cut line cut tooth load the real-time online monitoring,synchronous export analysis after storage.Experimental results show that the system is reliable,stable performance,can real-time dynamic testing of cutter tooth cutting force changes,through different cut line cut tooth time-cutting force change curves available:cutting force curve variation rule has the similarity,oblique cutting coal and rock,drum cutting tooth load whole curve peaks and troughs alternating form,cutting teeth with different cutting depth change of cutting force changing process;Same cutting resistance of greater than its feeding resistance,but its fluctuations are similar,have many irregular fluctuations;Single pick on the cutting resistance and traction resistance of instantaneous value obey the symmetry good Gamma distribution,the distribution parameters with pick in the cutting line spacing end plate distance relationship is a Fourier series,for the research on the rules of cutter tooth load spectrum provides a new method.